Macrostructure, spontaneity, and interactivity: an analysis of casual talk - Syafei, Muh; Nugroho, Kurniawan Yudhi; Madjdi, Achmad Hilal; Sulistyowati, Titis; Nurcahyo, Agung Dwi; Nuraeningsih, Nuraeningsih; Ekaningsih, Nur; Milad, Andurahman (EduLite: Journal of English Education, Literature and Culture, 2026)
This study provides a qualitative analysis of a casual talk between two male postgraduate EFL students, who are Indonesian, Javanese, and English-speaking close friends. The conversation, conducted spontaneously without prior planning, consists of 203 turns and forms 23 conversational story sequences. The findings highlight key aspects of casual conversation, including structural, interactive, and interpersonal features. Structurally, the dialogue follows adjacency pairs and the IRF (Initiate-Respond-Follow-up) pattern. Spontaneity is evident in filled pauses, repetitions, false starts, backtracking, incomplete utterances, and frequent use of conjunctions and fixed expressions. Interactivity is demonstrated through turn-taking, respectful silence, occasional interruptions, and discourse markers, with communication strategies employed to prevent breakdowns. Interpersonal engagement is reflected in the use of laughter and chuckles, fostering group solidarity. Coherence emerges through cooperative exchanges, where speakers provide relevant responses and comments. Additionally, negotiation occurs in both interpersonal exchanges and logical-semantic adjustments to maintain clarity and understanding. These findings suggest that the conversation builds engagement through laughter, coherence through cooperation, and clarity through negotiation, maintaining structured storytelling despite its casual tone. However, a key limitation of this study is its reliance on audio recordings, which excludes the analysis of gestures and facial expressions. Further investigation into diverse conversational contexts, participant relationships, and cultural influences could provide deeper insights into the dynamics of casual interactions